2016
DOI: 10.1016/j.clml.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Myxoma Virus Induces Ligand Independent Extrinsic Apoptosis in Human Myeloma Cells

Abstract: Introduction Multiple myeloma is a clonal malignancy of plasma B cells. While recent advances have improved overall prognosis, virtually all myeloma patients still succumb to relapsing disease. Therefore, novel therapies to treat this disease remain urgently needed. We have recently demonstrated that treatment of human multiple myeloma cells with an oncolytic virus known as myxoma results in rapid cell death even in the absence of viral replication; however, the specific mechanisms and pathways involved remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 58 publications
(47 reference statements)
2
26
0
Order By: Relevance
“…To facilitate studies into how MYXV treatment impacts MRD, we therefore sought to identify a murine MM cell which recapitulated the previously described response of human MM to MYXV treatment. 7,8 Four established murine MM cell lines: P3.6.2.8.1, MOPC-31C, MOPC-315, and MOPC-315.BM were either mock treated or infected with vMYX-GFP. The rate of infection (Figure 1a) and lytic potential (Figure 1b) of MYXV in each cell line was then compared with that seen in the human U266 MM cell line using flowcytometry and MTT assay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate studies into how MYXV treatment impacts MRD, we therefore sought to identify a murine MM cell which recapitulated the previously described response of human MM to MYXV treatment. 7,8 Four established murine MM cell lines: P3.6.2.8.1, MOPC-31C, MOPC-315, and MOPC-315.BM were either mock treated or infected with vMYX-GFP. The rate of infection (Figure 1a) and lytic potential (Figure 1b) of MYXV in each cell line was then compared with that seen in the human U266 MM cell line using flowcytometry and MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…6 Unfortunately, while this trial demonstrates that OV has tremendous promise for relapsed MM patients, application of the particular oncolytic measles virus tested is heavily restricted due to the high sero-prevalence of antimeasles immunoglobulin. In order to overcome this obstacle, our lab had previously investigated the antiMM potential of a nonhuman oncolytic agent, known as myxoma virus (MYXV), 5,7,8 whose natural tropism is tightly restricted to lagomorphs (rabbits). 9,10 This work demonstrated that, despite its nonhuman tropism, MYXV infection efficiently killed human MM cells by inducing a rapid apoptotic response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work to date on MYXV-mediated oncolysis of human MM has well characterized its ability to infect and kill human MM via a rapid induction of caspase-8-mediated apoptosis 20 . In stark contrast to this MYXV sensitivity of human MM, we show here that the murine MM cell line MOPC315.BM is uniquely resistant to infection by free MYXV because of its inability to bind MYXV virions, indicating that these cells are highly resistant to direct virus oncolysis, at least as assessed in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, MYXV selectively deletes MM cells from PBMCs or BM from patients ex vivo without harming CD34 + HSCs because normal stem cells are incapable of binding MYXV 15, 16, 17, 18, 19. The fate of MYXV-infected human MM cells is a rapidly induced apoptosis that is triggered through activation of the extrinsic caspase-8 pathway 20 . Previous studies investigating MYXV purging of human MM engrafted into irradiated NOD/Scid/IL2Rγ −/− (NSG) mice demonstrated that ex vivo pre-treatment of an allo-HSC transplant with MYXV maintains GVT effects in vivo without altering the engraftment of normal human HSCs into the recipients 15 .…”
Section: Introductionmentioning
confidence: 99%